EXPLORE THE THEME OF ALIENATION IN KIRAN DESAI’S THE INHERITANCE OF LOSS - Dhawan , Amit (International Journal of Psychosocial Rehabilitation, 2020)
There has been a noticeable shift in English writing’s focus to new compositions from previously colonised countries. The new scholars had to elevate their variegated interactions, which transcended race and diaspora, to a level that emphasised the acceptance of standard writing based on the human encounters documented in it. As a result, diasporic writing had the ring of authors who needed to establish their public character while also communicating their perspective on colonization’s effects. The compositions, among other things, moved, rebuilt, rethought, and restored cultural shapes. This focus looks at cultural traits and the possibilities of transculturalism as depicted in Kiran Desai’s work The Inheritance of Loss. The novel depicts the elation of globalization and the cultural issues looked by Indian workers in the West. Through her primary characters - Jemubhai, Biju, and Sai - Desai suggests actually transculturalism for her. The characters’ excursion through the post-provincial period in various cultural settings offers bits of knowledge into how the characters arrange the distinctions among societies and settings. This concentrate on fundamentally investigated the characters’ mentalities from the hybridity hypothesis viewpoint to unwind the creator’s voice regarding transculturalism. The three examination stages performed were to decide key story components related to the transcultural subject, to arrange the proof supporting the topic arose, and to decipher the discoveries utilizing the new historicism approach and considering the hybridity hypothesis. In light of the two inquiries raised on what cultural qualities deduced from the characters’ view and what thought of transculturalism passed on through the creator’s voice, this investigation discovered that the characters offered varying viewpoints on cultural pervasion and mixing. The creator recommended the outcomes of protection from cultural variety.